A case of oral cancer with delayed occipital lymph node metastasis: Case report. Issue 12 (30th July 2020) - Ono, Kisho; Yoshioka, Norie; Masui, Masanori; Obata, Kyoichi; Kunisada, Yuki; Okui, Tatsuo; Ibaragi, Soichiro; Kawai, Hotaka; Nagatsuka, Hitoshi; Sasaki, Akira
Abstract: Consideration of unexpected metastasis in patients who have undergone neck dissection with advanced tumors must be anticipated with careful follow‐up. Abstract : Consideration of unexpected metastasis in patients who have undergone neck dissection with advanced tumors must be anticipated with careful follow‐up.